A three year prospective study of functional and clinical outcomes of total hip replacement at a tertiary care hospital - Vijayanand, Addanki; Jayasomeswar, Narreddy (International Journal of Research in Orthopaedics, 2020)
Background: Hip joint is a crucial joint in the body whose function is essential for normal daily activities. Osteoarthritis of the hip cripples the daily functional capacity and total hip arthroplasty is considered to relieve the pain and increase the quality of life among these patients. The objective of present study was to assess the clinical and functional outcome in total hip replacement patients in terms of early joint function and stability of the hip joint and also to assess complications of procedures. Methods: A three-year prospective study was conducted on 58 cases that fulfilled the inclusion criteria. Ethical approval and consent were obtained for the study. Standard clinical and laboratory evaluation was performed on all the cases and the data was noted in Microsoft excel sheet and analyzed. Modified Harris hip scoring was done pre operatively and postoperatively and follow-up was done at discharge, 4th week, 6 months and one year. Results: Surgery was performed on 58 cases with age range 34-73 years and a mean of 43.58 years. Avascular necrosis was the main indication (55.2%). Maximum patient follow-up was 38 weeks. The mean preoperative score was 41.04 with minimum score being 10 and maximum being 76, postoperative score was 99.63 with minimum 64 and maximum was 109. Statistical significance was observed between preoperative and postoperative scores with regard to the parameters of pain, gait, functional activity and range of motion. Anterior thigh pain was the common postoperative complaint (15.5%). Conclusions: In conclusion, total hip replacement gives good clinical and functional outcomes. However, the outcomes are influenced by multiple factors which include indication for surgery, age of the cases, and type of prosthesis, operative technique and post-operative follow up.